COVID-19 Management and Arrhythmia: Risks and Challenges for Clinicians Treating Patients Affected by SARS-CoV-2 - Carpenter, Alexander; Chambers, Owen J.; El Harchi, Aziza; Bond, Richard; Hanington, Oliver; Harmer, Stephen C.; Hancox, Jules C.; James, Andrew F. (Frontiers in Cardiovascular Medicine, 2020)
The COVID-19 pandemic is an unprecedented challenge and will require novel therapeutic strategies. Affected patients are likely to be at risk of arrhythmia due to underlying comorbidities, polypharmacy and the disease process. Importantly, a number of the medications likely to receive significant use can themselves, particularly in combination, be pro-arrhythmic. Drug-induced prolongation of the QT interval is primarily caused by inhibition of the hERG potassium channel either directly and/or by impaired channel trafficking. Concurrent use of multiple hERG-blocking drugs may have a synergistic rather than additive effect which, in addition any pre-existing polypharmacy, critical illness or electrolyte imbalance, may significantly increase the risk of arrhythmia and Torsades de Pointes. Knowledge of these risks will allow informed decisions regarding appropriate therapeutics and monitoring to keep our patients safe.